Strategic approach to minimally invasive necrosectomy for necrotizing pancreatitis: technique, complications and predictors of outcome. Issue 3 (1st February 2021) - Mohapatra, Nihar; Sasturkar, Shridhar V.; Falari, Sanyam; Sandhyav, Rommel; Kumar, Niteen; Agrawal, Nikhil; Arora, Asit; Pamecha, Viniyendra; Chattopadhyay, Tushar K.
Abstract: Background: Minimally invasive retroperitoneal necrosectomy has been an integral component of 'step‐up' approach for infected pancreatic necrosis. Even though the clinical outcome of nephroscopic necrosectomy has been studied earlier, its predictor and morbidities following surgery have not been extensively evaluated. We aimed to evaluate the clinical outcome and early and late complications after percutaneous nephroscopic necrosectomy (PCNN). Methods: The pre‐ and intra‐operative as well as post‐operative and follow‐up data of severe pancreatitis patients undergoing PCNN were collected prospectively. Results: Out of 115 patients requiring intervention, 40 patients (34.78%) improved with percutaneous drain alone and another 40 proceeded for PCNN. After exclusion, 37 patients successfully underwent 48 sessions of PCNN. Median number of PCNN session was 1 (1–4). Early complications were seen in 21 (56.75%) patients and mortality was experienced in eight (21.62%) patients. On median follow‐up of 36 months, 12 (32.43%) patients experienced late complications. Persistent post‐operative pancreatic fistula was observed in six (16.21%) patients. Of these, three developed late‐onset pseudocyst, whereas one patient had disconnected duct syndrome. Seven patients experienced new‐onset diabetes. Age, severity of pancreatitis, preoperative organ failure and multiorgan failure were significant predictors of mortality on univariate analysis ( P  ≤ 0.05 for each). The logistic regression analysis revealed presence of multiorgan failure before surgery as the sole predictor ( P = 0.007; odds ratio 10.417; 95% confidence interval 1.759–61.672). Conclusion: Preoperative multiorgan failure was the most important predictor of mortality following PCNN. Late complications were seen in nearly one‐third of patients emphasizing the need for long‐term follow‐up. Abstract : A strategic step‐up approach for infected pancreatic necrosis leads to the resolution of disease in approximately 35% of patients by percutaneous drainage alone. Preoperative multiorgan failure is the most important predictor of mortality following percutaneous nephroscopic necrosectomy. Late complications after percutaneous nephroscopic necrosectomy is not uncommon and it occurs in nearly one‐third of the patients.